PHYSICOCHEMICAL CHARACTERISTICS AND ANTIMICROBIAL ACTIVITY TEST OF BACTERIOCINS ORGINATED FROM LACTIC ACID BACTERIA ISOLATES 17B ISOLATED FROM BALI CATTLE COLON - Putri, Nuria Fitrianti; Suardana, I Wayan; Utama, Iwan Harjono (Buletin Veteriner Udayana, 2018)
Lactic acid bacteria (LAB) is a microorganism that is not toxic and able to produce antimicrobial compounds, namely bacteriocins. This study aims to determine the physicochemical characterization of bacteriocins origin originated from lactic acid bacteria isolates 17B isolated from colon Bali cattle. The research was started by re-cultivation of isolates 17B and continued with production and precipitation of bacteriocins. Further tests were chemical and physical test that, followed by antimicrobial activity test of bacteriocin isolates 17B against Bacillus cereus FTCC 005. Data From this study are presented in tables or figure and analyzed descriptively. Results of study showed that LAB isolates 17B is a Gram-positive bacteria and catalase negative. The test also showed the bacteriocins produced isolates 17B as a protein compound indicated by the ninhydrin test positive, Molisch test negative and Lowry test positive with protein concentration was 0,11 µg/ml. Physical characterization tested using SDS PAGE showed that the test is negative. Antimicrobial activity test of bacteriocin isolates 17B showed that bacteriocin 17B has effectiveness against Bacillus cereus FTCC 005 as 18,92%.